EFFECTIVENESS OF TRANSBOUNDARY COLLABORATIVE CONSERVATION IN VIRUNGA NATIONAL PARKS - Nabalegwa M Wambede; Buyinza Mukadasi; Tiyo Christopher (Indonesian Journal of Geography, 2011)
The general aim was to assess the effectiveness of transboundary collaboration in thecontiguously adjoining protected areas of Virunga massive. The specific objectives were, a)to identify the role of different stakeholders in the management of transboundarycollaboration, b) to assess the level of collaboration between the three authorities andgovernments, c) to assess the participation of local communities in planning andmanagement of the natural resources, and d) to establish the effectiveness of the approach inmanaging natural resources. The study employed both the primary and the secondary datasources. The questionnaires were used to collect data from officers and the discussion withrelevant officials was conducted. A total 90 local community members were interviewed fromthe three countries. The secondary data were collected from management of MgahingaNational Park, Parc Nationaux des Volcano of Rwanda, Parc National des Virunga IGCPstaff and crossection of protected areas stakeholders and government institutions of the threecountries. The Results indicated that regarding the collaborative management between thethree authorities, it was found out that information exchange and joint patrol were the majoractivities. By 2003, in Uganda poaching had reduced to 1 case and the wire snare to 54which accounted for 2.3% and 8.8% respectively from the 23.3% and 19.6% in 1997.However the figures in Rwanda reduce slightly due to the security situation. It was alsodiscovered that the local communities of DR. Congo and Rwanda were highly involved inplanning of conservation activities that the case with Uganda.